DETERMINANTS OF EMPLOYEE PERFORMANCE IN PT. PERTAMINA (PERSERO) - Eka Candra Dinata; Dessy Adelin (Dinasti Publisher, 2020)
The purpose of this study was to determine and analyze: (1) Workload (2) Competence; (3) Performance Officer; and (4) The Effect of Workload and Competence on Employee Performance in the Production Department of PT. Pertamina either simultaneously or partially. The method used in this research is descriptive survey and explanatory survey, the unit of analysis in this study is employees in the Production Department of PT. Pertamina with a sample of 33 people. The type of investigation used is causality, and the time horizon in this study is cross-sectional. Based on the research results it was found that the workload experienced by the Production Department of PT. Pertamina is good, employee competence in the Production Department of PT. Pertamina in general can be said to be quite good. Employee Performance in the Production Department of PT. Pertamina is currently considered good. Workload and Competence affect the performance of employees in the Production Department of PT. Pertamina simultaneously and partially. However, partially Competence has a dominant effect on Employee Performance compared to Workload. Because Competency Performance is more dominant, it is prioritized in improving performance. Therefore the Production Department of PT. Pertamina is advised to increase the potential competencies that exist in each employee, so that they can work more professionally. Employee Performance at the Production Department of PT. Pertamina is currently considered good. Workload and Competence affect the performance of employees in the Production Department of PT. Pertamina simultaneously and partially. However, partially Competence has a dominant effect on Employee Performance compared to Workload. Because Competency Performance is more dominant, it is prioritized in improving performance.